2000
DOI: 10.1023/a:1006453915590
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma in situ of the female breast. 10 year follow-up results of a prospective nationwide study

Abstract: In a Danish nationwide prospective study of in situ carcinoma of the breast, a total of 275 women, treated with excision alone, were registered from 1982 to 1989. The series included 142 cases of ductal carcinoma in situ (DCIS), 100 cases of lobular carcinoma in situ (LCIS), 26 cases of DCIS+LCIS, and seven cases of atypical hyperplasia (AH). Within a median follow-up of 120 months, a crude recurrence rate of 28% (76 cases) was found, of which 53% (40 cases) recurred as invasive carcinomas (IC) and 47% (36 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
7

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 26 publications
1
79
0
7
Order By: Relevance
“…All in situ breast carcinomas are premalignant, being possible precursors to invasive disease capable of metastasis Page et al, 1985Page et al, , 2000Page and Dupont, 1990;London et al, 1992). The potential for progression to invasive cancer has been measured in earlier studies (Franceschi et al, 1998;Ottesen et al, 2000;Crocetti et al, 2001;Warnberg et al, 2001). However, the number of cases analysed previously was small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All in situ breast carcinomas are premalignant, being possible precursors to invasive disease capable of metastasis Page et al, 1985Page et al, , 2000Page and Dupont, 1990;London et al, 1992). The potential for progression to invasive cancer has been measured in earlier studies (Franceschi et al, 1998;Ottesen et al, 2000;Crocetti et al, 2001;Warnberg et al, 2001). However, the number of cases analysed previously was small.…”
Section: Discussionmentioning
confidence: 99%
“…Our data agree with earlier results, that the highest risk of invasive cancer is reached after 42 to 60 months after diagnosis of in situ lesions. (Franceschi et al, 1998;Ottesen et al, 2000;Warnberg et al, 2000Warnberg et al, , 2001Crocetti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These specimens included 47 cases of invasive ductal carcinoma (IDC), 40 cases of ductal carcinoma in situ (DCIS), 27 cases of atypical ductal hyperplasia (ADH), and 27 cases of proliferative disease without atypia (PDWA) including moderate and florid hyperplasia of the usual type. Pathological diagnosis was based on the work of Dupont et al 5) and of Ottesen et al 6) Classification of DCIS was based on the Consensus Conference on the Classification of Ductal Carcinoma In Situ in 1997. 7) Non-pathological breast tissues were available for examination in 13, 12 and 12 cases of DCIS, ADH and PDWA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One study, which included 26 patients with concurrent DCIS and LCIS, showed an overall recurrence rate of 35% in both patients with DCIS and those with DCIS and LCIS treated with surgery alone. 4 Provenzano et al 5 showed that the presence of concurrent ADH in 13 patients with DCIS did not significantly affect ipsilateral breast recurrence rates. Those investigators did not examine the effects of concurrent ADH and DCIS on the development of CBC.…”
Section: Discussionmentioning
confidence: 98%
“…However, compared with mastectomy breast-conserving sur-gery with radiation therapy is associated with a higher rate of local recurrence, with approximately half of all recurrences being invasive. 3 While several investigators have examined the effect of various tumor factors on ipsilateral breast carcinoma recurrence (IBCR) in patients with DCIS, few 4,5 have examined the effect of the presence of other lesions in the surrounding breast tissue on the rate of IBCR in patients with DCIS. To our knowledge, no studies have examined the effect of the presence of other lesions on the rate of development of contralateral breast carcinoma (CBC) in patients with DCIS.…”
mentioning
confidence: 99%